Collective bargaining on remunerations in the public sector and its link with the Government Budget Bill - Arce Ortiz, Elmer (2015)
In the present round table, leading specialists in Labour Law, Administrative Law and Constitutional Law comment the Peruvian Constitutional Court’s decision on case files 0003-2013-PI/TC, 0004-2013-PI/TC y 0023-2013-PI/TC. This decision addresses the prohibition of collective bargaining on remunerations in the public sector.